Socio-emotional wealth and family: revisiting the connection. (21st November 2016) - Schulze, William
Abstract : Purpose: In this commentary, the author aims to question whether the socio-emotional wealth (SEW) construct should be limited to family firms by noting that non-family owners and founders, i.e. those who yet have to involve family in their enterprise's operations, management or ownership, are also motivated to maximize their socioemotional wealth. Design/methodology/approach: The concept of SEW has generated significant traction in the family business literature and motivated an important body of work about how SEW alters decision-making in family firms. Professors Martin and Gomez–Mejia (this issue) extend past contributions by teasing apart complex relationships among the underlying dimensions of the construct. However, the domain of that paper, as well as the SEW construct, has heretofore been limited to family firms. The author builds his commentary on the work of Martin and Gomez–Mejia (this issue) to argue that the notion that SEW shapes decision-making in the owner controlled and owner-managed non-family firms, as well as family firms. Findings: The author's overarching conclusion is that there are several dimensions in which family interests materially alter decision-making but others in which family likely plays a moderating and possibly even a suppressor role. The surprising implication is that it may not be SEW per se that distinguishes family firms from non-family firms but rather how the family dynamic alters the influence of SEW on outcomes of interest. Originality/value: Acknowledging that personal and familial SEW have a common foundation allows one to sharpen the research focus and shift it from questions about how SEW might alter decision-making in family firms to questions about how the presence of family members alters the influence of SEW on decision-making in owner-controlled and owner-managed firms. This commentary explicates the argument and offers some suggestions about how this re-framing might allow for the extension of the SEW concept from the family firm to its influence on founder-managed and non-family firms.